The Impact of Metacognitive Awareness on Retention of Solubility and Solubility Product Equilibrium Concepts - Marisa; Erlina; Ulfah, Maria (Universitas Pendidikan Mandalika, 2025)
This study aims to describe the level of metacognitive awareness and learning retention regarding the concepts of solubility and solubility product among grade XI students at Senior High School 10 Pontianak, as well as to analyze the correlation between the two variables. The study population consisted of 94 students from classes XI A, XI B, and XI C, with a sample of 57 students selected through simple random sampling from classes XI B and XI C. Data were collected using a Metacognitive Awareness Inventory (MAI) questionnaire to measure metacognitive awareness and an essay test to assess learning retention. Descriptive and inferential statistical techniques were used for data analysis. The results showed that 35% of students demonstrated metacognitive awareness in the